The neuromuscular system of Chironomus vitellinus (Diptera: Chironomidae) - Roberto Reyes-Maldonado; Alonso Ramírez; Bruno Marie (PLoS ONE, 2026)
Chironomids are important laboratory model organisms used to assess toxicity in freshwater environments. Cell and tissue features are not commonly used as chironomid markers to detect toxicity, but they could be extremely helpful in identifying acute and chronic effects of pollutants. The nervous system is an excellent cellular candidate since it is reactive to toxic substances. However, a detailed description of the chironomid nervous system is required prior to considering it as a candidate for a cellular toxicity marker. The present study describes the central ganglia, nerves, axons, and the neuromuscular system of Chironomus vitellinus (Freeman, 1961) to facilitate its use as a model organism in environmental studies. We find that the structure of the C. vitellinus central nervous system is identical to that observed in other Chironomus larvae. We then focused our study on the first abdominal segment and labeled the 31 hemi-segmental muscles according to a nomenclature based on their position and orientation. We also characterized their innervation and assigned the nerves a nomenclature based on their terminals’ location in the muscle tissue. Finally, we investigated the neuromuscular junctions (NMJs) throughout this segment and defined four types of NMJs illustrating their great variability in size and shape. We selected a model NMJ, VEL 2, and quantified its mean bouton number and muscle size. Together with documenting a neurobiological system that could be informative to insects’ comparative biology, these results could help establish the Chironomus NMJ as an aquatic toxicity marker.